2014
DOI: 10.1038/ncomms5660
|View full text |Cite
|
Sign up to set email alerts
|

The crystallization water of gypsum rocks is a relevant water source for plants

Abstract: Some minerals, like gypsum, hold water in their crystalline structure. Although still unexplored, the use of such crystallization water by organisms would point to a completely new water source for life, critical under dry conditions. Here we use the fact that the isotopic composition of free water differs from gypsum crystallization water to show that plants can use crystallization water from the gypsum structure. The composition of the xylem sap of gypsum plants during summer shows closer values to gypsum cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 40 publications
(68 reference statements)
2
78
0
2
Order By: Relevance
“…Concentrations of these ions decreased downstream of sub‐catchments C and B, reflecting dilution with water from the crystalline terrain. Gypsum layers are generally known to be good water storages (i.e., Palacio, Azorín, Montserrat‐Martí, & Ferrio, ), and in sub‐catchments B and C, they contribute a significant part of the low‐flow discharge. In sub‐catchments B and C, 22% and 15%, respectively, of measured discharge comes from sedimentary rock layers.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of these ions decreased downstream of sub‐catchments C and B, reflecting dilution with water from the crystalline terrain. Gypsum layers are generally known to be good water storages (i.e., Palacio, Azorín, Montserrat‐Martí, & Ferrio, ), and in sub‐catchments B and C, they contribute a significant part of the low‐flow discharge. In sub‐catchments B and C, 22% and 15%, respectively, of measured discharge comes from sedimentary rock layers.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial soil water may be scarce during summer and these plants have low stomatal control (Palacio et al. ; León‐Sánchez et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if mediated by the dissolution of gypsum (Palacio et al. ), the release of gypsum crystallization water would imply a release of large amounts of Ca and SO 4 , which are toxic to most plants (Ruiz et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to halite and biofilm we included montmorillonite in our study, as it has been identified in the Martian soil (Poulet et al 2005;Vaniman et al 2014) and may form associates with bacteria being beneficial for their metabolism and survival (reviewed by Marshall 1975 andEngland et al 1993) as well as being a source of water supply. Palacio et al (2014) discusses even the crystallization water of other minerals like gypsum as a relevant water source for plants in an extremely dry environment. Because huge deposits of sulphate hydrates are well known to occur on the Martian surface Gendrin et al 2005) crystallization water may potentially be another water source for microorganisms on Mars.…”
Section: Introductionmentioning
confidence: 99%